Effect of high intensity interval and continuous swimming training on body mass adiposity level and serum parameters in high-fat diet fed rats - Rocha, Guilherme L. Da; Crisp, Alex H. [UNESP]; Oliveira, Maria R. M. De [UNESP]; Silva, Carlos A. Da; Silva, Jadson O.; Duarte, Ana C. G. O.; Sene-Fiorese, Marcela; Verlengia, Rozangela (Hindawi, 2016)
This study aimed to investigate the effects of interval and continuous training on the body mass gain and adiposity levels of rats fed a high-fat diet. Forty-eight male Sprague-Dawley rats were randomly divided into two groups, standard diet and high-fat diet, and received their respective diets for a period of four weeks without exercise stimuli. After this period, the animals were randomly divided into six groups (n=8): control standard diet (CS), control high-fat diet (CH), continuous training standard diet (CTS), continuous training high-fat diet (CTH), interval training standard diet (ITS), and interval training high-fat diet (ITH). The interval and continuous training consisted of a swimming exercise performed over eight weeks. CH rats had greater body mass gain, sum of adipose tissues mass, and lower serum high density lipoprotein values than CS. The trained groups showed lower values of feed intake, caloric intake, body mass gain, and adiposity levels compared with the CH group. No significant differences were observed between the trained groups (CTS versus ITS and CTH versus ITH) on body mass gains and adiposity levels. In conclusion, both training methodologies were shown to be effective in controlling body mass gain and adiposity levels in high-fat diet fed rats.